FAKTOR PENENTU STUNTING ANAK BALITA PADA BERBAGAI ZONA EKOSISTEM DI KABUPATEN KUPANG - Cahyono, Firmanu; Manongga, Stefanus Pieter; Picauly, Intje (Jurnal Gizi dan Pangan, 2016)
The aim of this study was to analyze difference and compare the determinants of stunting among under five years children considering different ecosystem in Kupang. It is an observational study using case control of under five children with and without stunting. There were 132 subjects chosen from lowland, middleland region, and mountainous ecosystem zones. Data was analyzed using Multiple Logistic Regression Analysis. The analysis resumes that determinants of stunting in lowland area is energy intake (p=0.002; OR=0.059; 95%CI:0.010-0.359), energy intake is a protective factor, in the middleland region is love and cares (p=0.002; OR=9.247; 95%CI:2.213-38.644) and sanitation (p=0.046; OR=2.832; 95%CI:1.020-7.860). Furthermore, the environmental sanitation as the factor in mountainous area (p=0.034; OR=3.978; 95%CI:1.112-14.230). The impact of stunting if left untreated will cause problems for generation in the future, for example impairment of mental development and physical growth, and it will end in poverty and the threat of life survival, so it need a proper intervention to handle it.Keywords: determinants, ecosystem zone, stunting